Theater Nuclear Weapons and the NATO Strategy of Flexible Response - Legge, J. M. (1983)
After more than a decade of comparatively little public interest in matters of nuclear strategy, the last few years have seen a resurgence of concern about the policy of nuclear deterrence that the North Atlantic Alliance has followed since the early 1950s. In Europe in particular, this concern has centered on the role of theater nuclear weapons in NATO strategy. This report briefly examines the way in which that strategy evolved from the foundation of the Alliance in 1949 to the formal adoption of the current "flexible response" strategy in 1967, with particular reference to the role of theater nuclear weapons. It then traces the development within the NATO Nuclear Planning Group of the more detailed doctrine concerning the role of theater nuclear weapons within the overall strategy, which led inter alia to the decision taken by NATO in 1979 to modernize the long-range component of the theater nuclear forces. The current flexible response strategy -- a compromise between European and American interests -- has been the subject of a good deal of criticism over recent years. The report examines the main arguments that have been advanced against the strategy, and considers the merits of various alternative strategies, including the proposals that NATO should adopt a "no-first-use" policy and that attempts should be made to establish a "battlefield nuclear free zone" in Europe. Particular attention is paid to the growing importance of public opinion as an influence on the future development of Alliance strategy. The conclusion is reached that, despite certain limitations, NATO is likely to adhere to its present strategy for at least the next decade. On the basis of this conclusion, the report finally considers ways in which the Alliance's theater nuclear stockpile might be adapted to meet the political and strategic needs of the 1980s. It is suggested that there is an urgent need to review the number of types of nuclear weapons based in Europe. ISBN 0-8330-0475-1